THEMATIC CONCERNS IN THE MEDITATIVE ARTWORKS OF PRATIKSHA APURV (International Journal of Food and Nutritional Sciences, 2022)
Meditation is an essential part of human life, both mentally and physically. It is associated with art from ancient times as both art and meditation belong to the creative state of the human mind. Artists have never failed to articulate their inner meditative selves through their works. It is evident from the works of Biren de in the 1960s, whose Tantric diagrams were made to aid meditation or visual symbolization. Raza's Bindu series was likewise a consequence of his contemplation on a specific dot on the blackboard. Many contemporary artists are using meditation as a subject matter in their works. This present study explores the thematic concerns in meditative artworks of contemporary artist Pratiksha Apurv and is concerned with how she has emptied her heart into this introspective theme in her artworks. A brief introduction to her early life, education, style & methodology, art career and stimulation behind these artworks will also be discussed.